Avaliação de condições operacionais na fermentação alcoólica VHG empregando diferentes cepas de Saccharomyces cerevisiae - Cruz, Mariana Lopes (2019)
The application of process engineering strategies for the development of high productivity fermentation systems is considered a key issue in the bioethanol industry. One strategy to increase the potential for ethanol production and to minimize the problems generated is the fermentation with high alcohol content that can be achieved through the use of more concentrated musts in total sugars (VHG). This technology can be used on an industrial scale for the production of ethanol and presents advantages such as obtaining higher levels of ethanol and minimizing production costs; in contrast they point to new challenges such as minimizing the effects of stress, osmotic and alcoholic, which yeasts are submitted. In this context, the present study aimed to study the fermentative profile of three industrial strains; PE-2, Y-904, and Ethanol Red in repeated batch fermentation processes at 20, 23, 25, 27 and 30 °C and flocculent yeast FL-20 in repeated batch and air-type reactor -lift, with emphasis on VHG fermentation conditions. Wines with ethanol contents varying from 16 to 18% (v/v) were obtained at the end of the fermentations of must containing 300 g/L of glucose by strains PE-2, Y-904, and Ethanol Red. The complete utilization of glucose and maintenance of cell viability in experiments with cell reuse showed that the fermentation of concentrated must for bioethanol production is feasible. With the FL-20 strain studied in repeated batch cycles in 8 consecutive cycles with cell recycling, a mean ethanol concentration of 130 g/L was obtained, with a productivity of 2.77 g/L.h. However, for the continuous reactor, the steady state for the dilution rate of 0.03h was reached with high values of residual glucose and ethanol concentration below that expected, in addition to the loss of flocculation capacity of the yeast. The influence of sugar concentration, cell concentration and temperature on VHG fermentation in a batch process fed with sugar cane molasses and broth was studied using the strain Y-904. It was observed that using the condition generated in the Central Compound Design (DCCR) that maximizes the studied variables (temperature of 27°C, 300 g/L of substrate concentration and 15% of cellular concentration), a productivity value of 4.42 g/Lh, 90% yield and 135 g/L ethanol. The equations provided by the DCCR with coefficient of determination in the range of 0.91 to 0.93; to describe the behavior of the fermentation process.